# Find the interval of convergence of the following series. frac{(x-4)^n}{3^n}

Question
Series
Find the interval of convergence of the following series.
$$\displaystyle{\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}$$

2021-02-23
Given the series:
$$\displaystyle{\sum_{{{n}={1}}}^{\infty}}{\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}$$
The nth term is given as:
$$\displaystyle{a}_{{n}}={\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}$$
Applying the ratio test, we get:
$$\displaystyle{L}=\lim_{{{n}\to\infty}}{\left|{\frac{{{a}_{{{n}+{1}}}}}{{{a}_{{n}}}}}\right|}$$
$$\displaystyle\Rightarrow{L}=\lim_{{{n}\to\infty}}\le{f}{t}{\left|{\frac{{{\frac{{{\left({x}-{4}\right)}^{{{n}+{1}}}}}{{{3}^{{{n}+{1}}}}}}}}{{{\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}}}}{r}{i}{g}{h}{t}\right|}$$
$$\displaystyle\Rightarrow{L}=\lim_{{{n}\to\infty}}{\left|{\frac{{{\left({x}-{4}\right)}^{{{n}+{1}}}}}{{{3}^{{{n}+{1}}}}}}\times{\frac{{{3}^{{n}}}}{{{\left({x}-{4}\right)}^{{n}}}}}\right|}$$
$$\displaystyle\Rightarrow{L}=\lim_{{{n}\to\infty}}{\left|{\frac{{{\left({x}-{4}\right)}^{{{n}+{1}-{n}}}}}{{{3}^{{{n}+{1}-{n}}}}}}\right|}$$
$$\displaystyle\Rightarrow{L}=\lim_{{{n}\to\infty}}{\left|{\frac{{{\left({x}-{4}\right)}}}{{{3}}}}\right|}$$
Now plugging the limit, we get:
$$\displaystyle\Rightarrow{L}={\left|{\frac{{{\left({x}-{4}\right)}}}{{{3}}}}\right|}$$
For series to converge:
$$\displaystyle{\left|{\frac{{{\left({x}-{4}\right)}}}{{{3}}}}\right|}{<}{1}$$</span>
$$\displaystyle{\left|{x}-{4}\right|}{<}{3}$$</span>
Hence the radius of convergence is:
$$\displaystyle{R}={3}$$
The interval of convergence is:
$$\displaystyle-{3}{<}{x}-{4}{<}{3}$$</span>
$$\displaystyle-{3}+{4}{<}{x}{<}{3}+{4}$$</span>
$$\displaystyle{1}{<}{x}{<}{7}$$</span>
Now checking for x=1, we get series:
$$\displaystyle{\sum_{{{n}={1}}}^{\infty}}{\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}={\sum_{{{n}={1}}}^{\infty}}{\frac{{{\left(-{1}\right)}^{{n}}}}{{{3}^{{n}}}}}$$
The above series converges since $$\displaystyle\sum{\left|{a}_{{n}}\right|}=\sum{\frac{{{1}}}{{{3}^{{n}}}}}$$ converges by geometric series test.
Now checking for $$\displaystyle{x}={7}$$, we get series:
$$\displaystyle{\sum_{{{n}={1}}}^{\infty}}{\frac{{{\left({x}-{4}\right)}^{{n}}}}{{{3}^{{n}}}}}={\sum_{{{n}={1}}}^{\infty}}{\frac{{{\left({3}\right)}^{{n}}}}{{{3}^{{n}}}}}={\sum_{{{n}={1}}}^{\infty}}{1}$$
The above is a diverging series.
Hence the interval of convergence is: $$\displaystyle{1}\leq{x}{<}{7}$$</span>
Interval of convergence of the series is :
$$\displaystyle{1}\leq{x}{<}{7}$$</span>

### Relevant Questions

Find the interval of convergence of the following series.
$$\frac{(x-4)^n}{3^n}$$
Find the​ series' interval of convergence​ and, within this​ interval, the sum of the series as a function of x.
$$\sum_{n=0}^\infty\left(\frac{x^2+4}{5}\right)^n$$
Radius and interval of convergence Determine the radius and interval of convergence of the following power series.
$$x-\frac{x^3}{4}+\frac{x^5}{9}-\frac{x^7}{16}+...$$
Series to functions Find the function represented by the following series, and find the interval of convergence of the series. (Not all these series are power series.)
$$\sum_{k=0}^\infty(\frac{x^2-1}{3})^k$$
Find the​ series' interval of convergence​ and, within this​ interval, the sum of the series as a function of x.
$$\sum_{n=0}^\infty\frac{(x-4)^{2n}}{36^n}$$
Find the interval of convergence of the power series.
$$\sum_{n=1}^\infty\frac{4^n(x-1)^n}{n}$$
$$\sum_{n=0}^\infty\frac{2^n(x-3)^n}{\sqrt{n+3}}$$
$$f(x)=\frac{3}{3+x}$$
$$\sum_{n=1}^\infty\frac{(-2)^nx^n}{\sqrt[4]{n}}$$
$$\sum_{n=1}^\infty\frac{x^n}{8n-1}$$